Negotiating authority and innovation: project-based learning and the changing professional landscape of madrasah teachers - Tambak, Syahraini; Yasin, Muhammad Dhiya’ul Haq bin Fatah; Lubis, Fauzi Sulistia; Tambak, Fauzi Al Mubarak (Jurnal Pendidikan Agama Islam Al-Thariqah, 2026)
Contemporary educational reforms increasingly emphasize student-centered pedagogies that transform traditional conceptions of teacher authority. Within Islamic education, however, such transformations raise important questions about how pedagogical innovation interacts with established moral and religious conceptions of teacher professionalism. This study examines how madrasah teachers negotiate professional authority while implementing project-based learning and how these negotiations reshape their professional identity within evolving educational contexts. Using a qualitative research design, data were collected through in-depth interviews with twenty-five madrasah teachers who had experience implementing project-based learning in classroom practice. The data were analyzed using thematic analysis to identify patterns in teachers’ interpretations of authority, pedagogical practice, and professional identity. The findings indicate that teachers increasingly reinterpret professional authority as dialogical pedagogical leadership characterized by facilitation, inquiry, and collaborative learning rather than hierarchical knowledge transmission. At the same time, teachers continue to ground their professional identity in Islamic educational traditions that emphasize moral guidance and ethical responsibility. These negotiations lead to the emergence of hybrid pedagogical practices that integrate project-based learning with Islamic moral pedagogy. The study contributes theoretically by proposing a culturally grounded framework of teacher professionalism in Islamic education that reconciles pedagogical innovation with religious educational values. The findings highlight the importance of developing context-sensitive pedagogical reforms that strengthen both educational innovation and the ethical foundations of madrasah teaching.